ANALYSIS OF GLOBAL VALUE CHAIN IN INDONESIA RUBBER EXPORT TO UNITED STATES VIEWED FROM AN ISLAMIC TRADING PRESPECTIVE - Tunggal, Aprilia Restuning; Zulham, Azwar Fadillah (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This study will examine further the problems of rubber export procedures through the concept of the global value chain in 2013, which led to cross-opinions both among elites and ordinary Indonesians, as a form of advice to the Indonesian government in the field of exports and effectiveness in business concepts, Indonesia and America The union has been cooperating since 2010 and in 2013 the value of Indonesian exports to America in the rubber sector specifically decreased by 14.5%, therefore there were two issues behind the emergence of the concept of global value chain to change in terms of product design, marketing, and the process and export process from Indonesia to the United States with the legality of the government and how the concept of trade in Islam which includes Tawhid, Maqasidh Syariah, Rububiyah, Keadilan, sees this phenomenon. Thus, through the Islamic trade approach, Indonesian rubber exports to America do not guarantee freedom from the elements of maysir, usury and gharar which are strongly opposed in Islamic law, therefore the concept of trade in Islam based on the Al-Quran surah An-Nisa is offered as an alternative solution formula in realize justice and benefit in the process of each trade, especially for good policies for the Indonesian government.